Do Contract Remedies Affect Efficient Renegotiation? An Experiment - Maria Bigoni; Stefania Bortolotti; Francesco Parisi; Xin Zhang (Institute of Labor Economics (IZA), 2024)
Rational parties enter into a contract if the agreement is mutually beneficial. However, after the contract is formed, changes to the costs and/or benefits of performance may render the original contract undesirable. In this paper, we carry out an incentivized experiment to study the effect of alternative remedies on the parties' ability to renegotiate their contractual obligations. After entering into a contract, experimental subjects observe symmetrical changes to the original costs and/or benefits, which create a misalignment of their performance vs. breach incentives. Renegotiation of the original contract would allow parties to realign their interests and to capture some additional surplus. Our experimental design compares the effects of damage and specific performance remedies on the parties' ability to renegotiate. Our results confirm Coase' (1960) irrelevance of remedies proposition, providing novel insights for the choice of contract remedies in the face of possible market shocks.
Keywords: K12; K41; C90; D86; D91; 330; efficient breach; contract remedies; specific performance; damages